Niger : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2013)
Niger understands the need to adopt a long-term strategy capable of optimizing natural and human resources to promote sustainable economic and social development and inclusive growth. The government has renewed planning efforts in the preparation of three principal strategic documents. These three strategic planning tools are complementary, and the government is committed to implementing them so that they interact with each other synergistically while ensuring dynamic linkages between short-, medium-, and long-term programs.